Good English Learners’ Strategies in Building up Speaking Skill - Indah, Yani Awalia; Putra, Juang Rudianto (ENGLISH JOURNAL, 2016)
In the attempt of building up speaking skill, English language learners need to possess and frequently execute certain learning strategies when doing the practice. These strategies could be adapted from those good English learners as they have gone in through the process of learning the language and now become successful (Damayanti, 2009). These of course will give learners an appropriate example of how to sharpen their speaking skill. Therefore, this study was carried out to identify the strategies used by good English learners in improving speaking skill. Using qualitative method, the research instruments employed were questionnaire, interview and observation. This study was done at the English department, the faculty of teacher training and educational sciences, Ibn Khaldun University Bogor. The participant was taken from the students of fifth semester. It consisted of five participants. From the study, it could then be concluded that the strategies used by good English learners in building up speaking skill were practicing regularly, making dialogue or even monologue, memorizing vocabulary, and feeling confidence to use the language. As the learning facilitator, teacher is also strongly suggested to know kind of learning strategies preferred by his students and create optimal learning environment. This is aimed to lead students achieve their learning succes.